PENGARUH FAKTOR ABIOTIK TERHADAP HUBUNGAN KEKERABATAN TANAMAN Sansevieria trifasciata L - Anita Restu Puji Raharjeng (Biota, 2015)
Sansevieria trifasciata L. (Agavaceae) is a plant that can be grown in all places, both in lowland and highland. Malang with its heights ranging from the coast to 1,200 m asl is interesting to be studied because it has great potential for the diversity of Sansevieria. Altitude affects the soil and climatic conditions, so that the altitude affects the phenotype of the plant. The aim of this study was to investigate the influence of abiotic factors on the relationship of Sansevieria trifasciata L. that grow at different altitude. Sansevieria samples were taken from 23 locations in Malang in lowland and highland. The observation was on the morphology, and it abiotic factors, ie altitude, temperature, humidity, soil pH, precipitation, and light intensity. The results showed that the abiotic factors have little effect on the morphology of Sansevieria trifasciata L. that grows in the highlands and lowlands.